MANAJEMEN BERBASIS SEKOLAH DALAM PENGELOLAAN PEMBIAYAAN SEKOLAH DI SD NEGERI 4 KOTA BANDA ACEH - Susilawaty .; Cut Zahri Harun; Khairuddin . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: Implementation of School-based management (SBM) is one attempt to raise the quality of education in an effective and productive. A good financial management as one of the MBS can expedite the implementation of the learning process. This study aims to reveal and analyze the financial management of SD Negeri 4 Banda Aceh. This research uses descriptive method with qualitative approach. Data collection techniques used interviews and documentation studies. Subjects in this study were school principals, representatives, committees and four elementary school teachers Banda Aceh. The research results showed that the Planning financing in SD Negeri 4 Banda Aceh compiled based on plan school development and it’s part of operationalplans the annual. Financing plan in the SD Negeri 4 Banda Aceh include budgeting for competency development activities, curriculum development, development of the learning process, educators and educational staff development, school facilities and infrastructure development, development and implementation of school management, development and excavating the source of funds for education, and development and systematic assessment implementation. The preparation of financial planning was based on the composition of a very urgent priority and precedence in its budget each year. Implementation or use of a series of events beginning with the budget and approval to ensure that funds are spent as planned, carried out by utilizing the available resources, and funds not spent for activities that are not approvedor provided to the receiving party without consent. Evaluation is done every quarter or per semester. Funds are used properly accountable to the sources of funds by the city, province, central although parents / guardians and the community.Keywords: School-Based Management, Manage Financing